FAKTOR FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION KARYAWAN PADA HOTEL BINTANG TIGA DI KOTA PADANG - Shelinda Rahman; Harif Amali Rivai (Journal of Management and Business Review, 2020)
Human resources have an important role in an organization both large and small scale organizations. The world of tough competition the organizations try to minimize their turnover ratio and save their cost, turnover cost consists of re-recruiting employees and retraining costs. The purpose of this research is to understand and analyze the effects of training satisfaction, pay satisfaction and job satisfaction to employee turnover intention with organizational commitment as a mediating variable in the three-star hotel employess in Padang city. With a total of 140 respondents the sample validity testing was carried out by loading factor and average variance extracted (AVE) while the reliability testing used an internal consistency test based on composite reliability values. Validity test with loading factor shows a valid value. Reliability testing with internal consistency test has composite reliability values that meet the criteria. Based on the test results, all variable indicator statements have met the criteria of validity and reliability. Hypothesis test results with SmartPLS show that organizational commitment, training satisfaction and salary satisfaction have a negative and significant effect on turnover intention. Organizational commitment mediates the relationship of training satisfaction, salary satisfaction, and job satisfaction on turnover intention.